Przekształcenia w strukturach gospodarczych wschodnich landów RFN - Czech-Rogosz, Joanna (Economic Structures of East Germany, 2009)
The problem of unfinished unification of East and West Germany is becoming more and more important because of the crisis affecting German economy in 2009. The article characterizes particular issues from the point of view of current economic situation and economic structures of East Germany.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 569-577